Cartilage metabolism in the injured and uninjured knee of the same patient. Issue 12 (December 1994) - Dahlberg, L; Roos, H; Saxne, T; Heinegård, D; Lark, M W; Hoerrner, L A; Lohmander, L S
Abstract : OBJECTIVE--To examine if unilateral knee injury affects the synovial fluid concentrations of aggrecan fragments, cartilage oligomeric matrix protein (COMP) fragments, stromelysin-1, and tissue inhibitor of metalloproteinases-1 (TIMP-1) in the contralateral uninjured knee. METHODS--Synovial fluids from the injured and uninjured knees were obtained at different times in a group of patients after unilateral knee trauma. Serum samples were obtained on the same occasion. Concentrations of aggrecan fragments were determined by precipitation with Alcian Blue; those of COMP fragments, stromelysin-1, and TIMP-1 were measured by immunoassay. Concentrations were compared with those in a reference group of 10 healthy volunteers. RESULTS--Immediately after knee injury, concentrations of aggrecan fragments, COMP fragments, stromelysin-1 and TIMP-1 were increased in the synovial fluid of the injured knee. However, concentrations of aggrecan and COMP fragments, and stromelysin-1 increased also in the contralateral uninjured knee immediately after injury, but less than in the injured knee. Subsequently, the concentrations of all markers decreased in the synovial fluid of the injured knee, but remained unchanged in the uninjured knee. The concentration of aggrecan fragments in the injured knee decreased to less than that in the uninjured knee in the chronic phase. Serum concentrations of COMP were much smaller than those in synovial fluid. CONCLUSIONS--The increased concentrations of aggrecan and COMP fragments and stromelysin-1 in the joint fluid of the contralateral, uninjured knee following unilateral knee injury, compared with concentrations in healthy reference knees, suggest changes in joint cartilage metabolism in both knees following unilateral knee injury. The mechanisms for these changes are unclear. The low serum concentration of COMP makes it less likely that there is any significant 'exchange' of molecular makers between the knees. A further consequence of these findings is that the contralateral knee cannot be recommended as the only control joint in studies of matrix metabolism in patients with unilateral knee injury.